RUANG PERANTARA MANUSIA DENGAN HEWAN - Jennifer Chandra; Sidhi Wiguna Teh (Jurusan Arsitektur dan Perencanaan, 2019)
Millennials are currently facing the 6th stage of Psychosocial Crisis which revolves around the nature of relationships. Success in going through this phase will lead them to love and intimacy, while failure will result in isolation and in some cases might lead to depression and other mental health problems. Animal Assisted Therapy has been proven to be effective in the correction of an individual’s relationship orientiation. A space is needed to accommodate these programs and activities in which humans and animals are concerned. This journal will be discussing the design of the previously mentioned required space. Discussion will include analysis and syntesis of the datas collected, and also the final design output. Abstrak Milenial sedang menghadapi krisis psikososial ke-6 yang berkaitan dengan hubungan relasi dengan pihak-pihak lain. Keberhasilan dalam melewati tahap ini akan membentuk sebuah individu yang mengenal cinta dan bahagia, kegagalan dalam melewati tahap ini adalah isolasi yang dapat menjurus kearah masalah mental seperti depresi. Terapi hewan telah dibuktikan dapat membantu untuk memperbaiki hubungan manusia dan juga memberikan dampak yang sangat baik pada sifat dari hubungan tersebut. Sebuah wadah dibutuhkan untuk mewadahi kegiatan tersebut. Artikel ilmiah ini akan membahas mengenai perancangan sebagai wadah kegiatan. Pembahasan akan meliputi analisis dan sintesis dari data-data yang telah dikumpulkan, dan output perancangan.